2023
DOI: 10.3390/biomedicines11102684
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Optimal Hydration in Patients with Heart Failure—Not Always Too Much Fluid

Andrzej Wittczak,
Maciej Ślot,
Agata Bielecka-Dabrowa

Abstract: Heart failure (HF) is a leading cause of morbidity and mortality and a major public health problem. Both overhydration and dehydration are non-physiological states of the body that can adversely affect human health. Congestion and residual congestion are common in patients hospitalized for HF and are associated with poor prognosis and high rates of rehospitalization. However, the clinical problem of dehydration is also prevalent in healthcare and community settings and is associated with increased morbidity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 134 publications
0
2
0
Order By: Relevance
“…Common measures for assessing body hydration levels, such as total body water content and plasma/urine osmolality, are not ideal for indicating homeostatic hyper-, normo-, or hypo-hydration status in an individual. This is because they rely on population-derived ranges that cannot determine whether specific values of body hydration in individuals are within or outside their individual homeostatic ranges, as they do not assess compensating or regulating physiological responses to those hydration states 37 . In patients, medical histories, clinical features, and physical examinations, often with referral to specialists, along with the empiric ('trial and error') treatment method suggested by contemporary hypertension treatment guidelines, remain the standard for stratifying patients into these two different types of hypertension and determining their distinct care 38 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common measures for assessing body hydration levels, such as total body water content and plasma/urine osmolality, are not ideal for indicating homeostatic hyper-, normo-, or hypo-hydration status in an individual. This is because they rely on population-derived ranges that cannot determine whether specific values of body hydration in individuals are within or outside their individual homeostatic ranges, as they do not assess compensating or regulating physiological responses to those hydration states 37 . In patients, medical histories, clinical features, and physical examinations, often with referral to specialists, along with the empiric ('trial and error') treatment method suggested by contemporary hypertension treatment guidelines, remain the standard for stratifying patients into these two different types of hypertension and determining their distinct care 38 .…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods are less suitable for individuals sampled from a general population 39 . Thus, the insufficiencies in traditional metabolic and clinical indicators of individually optimal body hydration states have been recognized as a problem in cardiovascular medicine 37 , 40 .…”
Section: Introductionmentioning
confidence: 99%